(untitled) (Journal of Atomic and Molecular Sciences, 2021)
We present the distorted wave Born approximation (DWBA) for electron impact excitation and a method to calibrate the DWBA. With the calibrated DWBA, the differential cross sections (DCS) for excitation of H and He^+ from 1s to 2s and 2p are calculated and the results are compared with the absolute experimental measurements for H at incident energies of 50 eV and 100 eV. It has been found that the theoretical results are in very good agreement with the experiment, which confirms the validity of the calibration procedure. This work prepares an efficient theoretical method for numerical simulations of non-sequential double ionization of He in strong laser pulse in which laser-induced electron impact excitation of He^+ is involved.